The prevalence of hypogonadism in diabetic men in Isfahan Endocrine and Metabolism Research Center, Isfahan, Iran - Mirzaei, Mohammad Reza (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVE: Low testosterone, with or without symptoms, reported in diabetic men in some studies. We investigated the prevalence of hypogonadism in Iranian type 2 diabetic men. MATERIALS AND METHODS: Total testosterone (TT) and sex hormone binding globulin (SHBG) concentrations were measured in 247 diabetic men >30 years who had symptoms of androgen deficiency, according to ADAMs questionnaire. The correlation between some parameters and total, free and bioavailable testosterone levels was determined using Pearson correlation coefficient. Free and bioavailable testosterone were calculated by electronic calculator. Four patients were excluded because of high testosterone level, due to unreported androgen use. Overt hypogonadism was defined as total testosterone ≤8 nmol/l or calculated bioavailable testosterone (cBT)≤2.5 nmol/l and borderline hypogonadism was considered as TT 8-12 nmol/l or cBT 2.5-4nmol/l. RESULTS: The mean and SD of age was 59 (9.3) years. The mean TT, calculated free testosterone (cFT), and cBT and SHBG levels were 4.81 (1.7) nmol/l, 0.11 (0.06) nmol/l, 2.42 (1.17) nmol/l and 36.15 (18.3) nmol/l, respectively. According to TT and cBT, overt hypogonadism observed in 7.4% and 61.6% of men, respectively, and the prevalence of borderline hypogonadism was 9.9% and 36%, respectively. cFT ≤0.16 nmol/l found in 227 diabetic men (96%). Hypogonadism (TT ≤12 nmol/l) was not correlated with obesity, smoking, age,duration of diabetes, blood pressure, and HbA1c. CONCLUSION: Hypogonadism is highly prevalent in type 2 diabetes men.